Health information acquisition behavior and its correlates among food delivery workers in Shanghai city, 2021: a cross-sectional survey - Kai KANG; Jieyi LIU; Zhenyi WU; Xinfeng PAN; Yuan DING; Pinpin ZHENG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo comprehend the present situation and influential factors of health information acquisition behavior among food delivery workers in Shanghai for developing health communication strategies for the occupational group. MethodsA web-based survey was conducted from October to December 2021 among a purposive sample of 1 065 food delivery workers recruited across 16 districts in Shanghai city, utilizing a self-designed questionnaire. ResultsAmong 1 027 valid respondents, 94.84% reported actively paying attention to health information, principally on knowledge about disease prevention, healthy diets and first aid; 78.03% reported obtaining the information mainly through social platforms such as WeChat and TikTok; and 38.40% reported getting the health information in text and comic form. The results of univariate analysis showed that gender, education level, presence of chronic diseases, self-rated health condition in the past year, and mode of employment were influencing factors for active acquisition of health information (P < 0.05 for all). The results of the multivariate logistic regression analysis revealed that individuals with chronic diseases (odds ratio [OR] = 4.35, 95% confidence interval [95%CI]: 1.35 - 5.88) and those who reported poor self-rated health in the previous year (OR = 7.14, 95%CI: 2.38 - 20.01 for general health, OR = 6.25, 95%CI: 1.04 - 16.67 for poor health, and OR = 50.00, 95%CI: 3.85 - 137.81 for very poor health) exhibited a significantly higher likelihood of actively seeking out health information (P < 0.05 for all). ConclusionThe primary influencing factors on the voluntary behavior of health information acquisition among food delivery workers are their chronic disease status and recent self-assessment of health. Expanding the channels for accessing health information, utilizing new media communication, and diversifying communication formats can effectively promote the development of food delivery workers 's behavior in acquiring health information.